An invisible workforce: The neglected role of cleaners in patient safety on maternity units - Cross, Suzanne; Gon, Giorgia; Morrison, Emma; Afsana, Koasar; Ali, Said M.; Manjang, Tina; Manneh, Lamin; Rahman, Atiya; Saxena, Deepak; Vorah, Kranti; Graham., Wendy J. (Taylor & Francis Online, 2022)
This article was published in the Global Health Action [© 2019 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0/) ] and the definite version is available at:https://doi.org/10.1080/16549716.2018.1480085 The Journal's website is at: https://www.tandfonline.com/doi/full/10.1080/16549716.2018.1480085